Cognition for coaches: A curriculum for coaches working in physical activity programming for veterans. (2nd January 2023) - White, Shannon C.; Hill, John C.
ABSTRACT: Veterans returning home from duty are affected in ways which are both visible and unseen. More importantly, veterans transitioning back to civilian life are susceptible to a loss of social support and isolation from their communities. Based on the success of sport as a curative factor for wounded veterans, this curriculum framework seeks to prepare coaches to appropriately train and coach athletes who are wounded veterans. Additionally, this curriculum conceptualizes the coach as the gatekeeper for enhancing a sense of community and social capital among participants by increasing his or her awareness of participant personalities and identities, in conjunction with their military experiences as well as those associated with reentry into civilian life.